MENGUKUR PERAN ZAKAT TERHADAP KESEJAHTERAAN SOSIAL DENGAN PENDEKATAN INDEKS ZAKAT NASIONAL (STUDI CASE BAZNAS KABUPATEN SIAK) - Solahuddin Al-Ayubi Solahuddin; Dikky Wahyudi; M. Fikriadi; M. Ridho Al Fathan. S (Mumtaz Publishing, 2023)
This study aims to determine the role of zakat on people's welfare in the Siak Regency. The research method used is mixed (mixed method). Data collection using interviews and questionnaires. The sample was selected using a simple random sampling technique, while data analysis was carried out using the National Zakat Index (IZN) approach. The results of this study indicate that the role of zakat on people's welfare in Siak Regency has a significant effect, this can be seen from the results of the index value of the micro dimension which ranges from 65%. In addition, zakat also has a significant effect on the social finance index, the development index, and also the community independence index in Siak Regency.